1985
DOI: 10.1128/aac.27.5.798
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between butirosin biosynthesis and sporulation in Bacillus circulans

Abstract: The relationship between butirosin biosynthesis and certain biochemical characteristics related to sporulation in a strain of BaciUus circulans NRRL B-3313 was examined. The cellular content of dipicolinic acid increased while the amount of poly-13-hydroxybutyrate decreased with changes in antibiotic productivity.Oligosporogenous mutants failed to synthesize the antibiotic and to degrade poly-4-hydroxybutyrate. These observations suggest that spore formation may be related to antibiotic production in this stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The rapid drop in cell dry weight (CDW) was due to the cell growth decline phase. The slight decrease in PHB production could be due to the fact that the microorganism could synthesize PHB until the sporulation stage and after that the remaining bacterial cells consume the PHB (Benoit, 1990;Nam and Ryu, 1985). Yilmaz et al., (2005) reported that some B. sphaericus strains were able to synthesize PHB up to 32.55% (w/v).…”
Section: Resultsmentioning
confidence: 99%
“…The rapid drop in cell dry weight (CDW) was due to the cell growth decline phase. The slight decrease in PHB production could be due to the fact that the microorganism could synthesize PHB until the sporulation stage and after that the remaining bacterial cells consume the PHB (Benoit, 1990;Nam and Ryu, 1985). Yilmaz et al., (2005) reported that some B. sphaericus strains were able to synthesize PHB up to 32.55% (w/v).…”
Section: Resultsmentioning
confidence: 99%
“…paromomycinus . Aminoglycoside production media (A6 media) [ 55 ] was also prepared and used in this study and was composed of (g/L): soybean meal 30, CaCO 3 5, NH 4 Cl 4 and glycerol 40 ml/L and distilled water to 1 L. The media pH was initially adjusted to 7.…”
Section: Methodsmentioning
confidence: 99%
“… a Soybean meal [21] b Soybean meal-yeast extract glucose [22] c Tryptone-yeast extract [23] d Yeast extract medium [24] e Beef extract medium [21] f Aminoglycoside production medium [25] g ryptic Soy Broth (TSB) [15] h soyabean casein digest broth l Absence of ingredient…”
Section: Methodsmentioning
confidence: 99%